Tinjauan Atas Implementasi Prosedur Audit Kas dan Setara Kas pada Kantor Akuntan Publik di Sidoarjo - Riski Famiyanti; Acynthia Ayu Wilasittha (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The cash and cash equivalent audit procedure is a series of steps that the auditor takes to verify the existence, completeness, accuracy, and presentation of an entity's cash and cash equivalents in the financial statements. The research was carried out with the aim of understanding the process of implementing cash and cash equivalent audit procedures at the KAP Djoko, Sidik & Indra Sidoarjo Branch. The research was conducted using a descriptive analysis method by collecting two data sources, namely primary data obtained from interviews, observations and documentation directly during the audit, while secondary data was collected from several publications including articles, journals and internet sites that correspond to the research topic. The research results prove that the implementation of cash and cash equivalent audit procedures carried out at the KAP Djoko, Sidik & Indra Sidoarjo Branch for clients is in accordance with the theory put forward by Sukrisno Agoes. Through this research, it is hoped that interested parties can gain understanding and insight regarding cash and cash equivalent audit procedures in theory and real practice in the world of work.